Accountability in extraterritoriality : a comparative and international law perspective - Ireland-Piper, Danielle (Edward Elgar Publishing, 2017)
Nation states are increasingly asserting jurisdiction over criminal offenses that occur extraterritorially. In some instances, this can cause political tension and legal uncertainty, as the principles of jurisdiction under international law do not adequately resolve competing claims. In that context, this book considers principles of jurisdiction and mechanisms by which to achieve jurisdictional restraint under international law, including the possibilities presented by the abuse of rights doctrine. Utilising a comparative approach, this book explores principles of jurisdiction, first under international law, and then in a comparative constitutional law context. Specifically, Danielle Ireland-Piper explores the ways in which domestic constitutional courts in Australia, India and the United States adjudicate extraterritorial criminal jurisdictions. Groundbreaking sections explore the abuse of rights doctrine in a common law context and the relationship between individual rights and the assertion of extraterritorial jurisdiction. While this is a research monograph that will likely interest legal scholars and researchers in international relations and political science, it will also appeal to government policy-makers and judicial decision-makers, particularly given the increased reliance by governments on extraterritorial regulation of transnational crime.